Predicting entrepreneurial intention across the university. Issue 7 (12th August 2019) - Bell, Robin
Abstract : Purpose: The purpose of this paper is to quantify the relative importance of four key entrepreneurial characteristics identified in the literature (proactiveness, attitude to risk, innovativeness and self-efficacy) in predicting students' entrepreneurial intention (EI) across a range of faculties offering different subjects at a UK higher education institution (HEI). This approach will help to identify whether there are variations across the faculties in the predictors of EI. This enables recommendations to be made with regard to the development of educational delivery and support to encourage and develop the specific predictors of EI within the different subject areas. Design/methodology/approach: This research uses a 40-item questionnaire to obtain information on students' demographics, entrepreneurial characteristics and EI, based on a five-point Likert-type scale. Principle component analysis, correlation analysis and multiple hierarchical regression analysis are used to analyse the data from 1, 185 students to develop models which predict EI for each of the six faculties. Findings: Individual models which predict EI are developed for each of the six faculties showing variations in the makeup of the predictors across faculties in the HEI. Attitude to risk was the strongest predictor in five of the six faculties and the second strongest predictor in the sixth. The differences, together with the implications, for educational approaches and pedagogy are considered. Originality/value: This research breaks down the level of analysis of EI to the individual faculty level in order to investigate whether different entrepreneurial characteristics predict EI in different academic disciplines across a UK HEI. This enables entrepreneurship educational approaches to be considered at a faculty level rather than a one size fits all approach.